2008
DOI: 10.1007/s10493-008-9216-0
|View full text |Cite
|
Sign up to set email alerts
|

First detection of Varroa destructor resistance to coumaphos in Argentina

Abstract: In Argentina, studies on Varroa destructor resistance to coumaphos are still unknown. At present, high infestation levels of V. destructor are being detected in colonies of Apis mellifera after treatment with this acaricide. The aim of the present study was to determine the LC50 of coumaphos in V. destructor from four apiaries with high mite density after treatment with coumaphos. The LC50's were 112, 319, 127 and 133 microg/Petri dish for mites from the four apiaries. Significant LC50 differences were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 5 publications
4
45
0
6
Order By: Relevance
“…Furthermore, a recent study performed in Argentina by Medici et al (2015) documented a positive correlation between the resistance index of coumaphos in V. destructor and the levels of the organophosphate found in beeswax. These studies and the reports of phenomena of resistance to acaricides in Argentina (Maggi et al , 2009 provided enough evidence to correct sanitary plans after being reported to public health agencies and beekeepers in order to modify the use and rotation of acaricides. Uruguay and Chile still require more in-depth studies related to this topic; the fact that the presence of acaricides in beeswax affects the susceptibility of V. destructor (Medici et al 2015) is extremely worrying.…”
Section: Varroosismentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, a recent study performed in Argentina by Medici et al (2015) documented a positive correlation between the resistance index of coumaphos in V. destructor and the levels of the organophosphate found in beeswax. These studies and the reports of phenomena of resistance to acaricides in Argentina (Maggi et al , 2009 provided enough evidence to correct sanitary plans after being reported to public health agencies and beekeepers in order to modify the use and rotation of acaricides. Uruguay and Chile still require more in-depth studies related to this topic; the fact that the presence of acaricides in beeswax affects the susceptibility of V. destructor (Medici et al 2015) is extremely worrying.…”
Section: Varroosismentioning
confidence: 90%
“…In this context, mite populations that are resistant to amitraz, flumethrine, and coumaphos have emerged in SA (Maggi et al 2009(Maggi et al , 2011Aldea and Rodríguez 2014). On the other hand, a decreased efficacy of fluvalinate has been detected in Uruguay and Argentina in zones where it has been used for many years (Fernández and García 1997;Invernizzi et al 2011).…”
Section: Varroosismentioning
confidence: 99%
“…Coumaphos proved very stable in honey, moved quickly to the wax because of its strong lipophilic character and remained there in significant concentrations even after melting of the wax (Krieger, 1991). Reports that mites became resistant to coumaphos have already been published (Maggi et al, 2009;Petis, 2004).…”
Section: Coumaphosmentioning
confidence: 99%
“…Thus, N. ceranae is considered one of the factors that contribute to colony depopulation also associated with the recent colony collapse disorder (CCD) (Oldroyd, 2007;Higes et al, 2008;Paxton, 2010). In order to overcome the pathologies, continuous chemical applications have been employed incorrectly producing undesirable results such as resistant strains (Maggi et al, 2009(Maggi et al, , 2010(Maggi et al, , 2011 and residues on beehive products (Bogdanov, 2006;Medici, 2010;Simion et al, 2011). Consequently, antibiotics have been banned in most EU member states.…”
Section: Introductionmentioning
confidence: 99%